Marginal Majority at The Postcolonial News Agency: Foreign journalistic hires at the Associated Press. (2nd January 2016) - Seo, Soomin
Abstract : Using 74 archival interviews with former and current employees, this paper explores the sociology of journalistic hires in foreign bureaus at the Associated Press. It finds that locally hired staff play crucial roles in foreign bureaus by providing the often-inexperienced home staffers with local context and linguistic help. The locals thus become an integral part of the Associated Press' foreign coverage, which became more in-depth and contextual after the 1960s, in tandem with the rest of American journalism. However, a discriminatory framework in compensation and status—which can be traced back to the colonial days—applies for the locals, a framework exacerbated by the paternalistic rhetoric in its tradition of the "Marine Corps of journalism." In recent decades, however, the organizational culture is changing, with the increased employment of multicultural and multilingual journalists, foreign and local.